Categorisation and Relevance of Policing Models in the Literature - Harmati, Barbara (Magyar Rendészet, 2022)
This article presents a review of keywords available in the literature focusing on policing models, with the aim of evaluating how authors and KeyWords Plus classify these models. The literature shows that even though several policing models have been published since the 1970s, there is no common categorisation of the different approaches. This, however, would help unifying the area. A strong relationship between third-party policing, problem-oriented policing, community policing, evidence-based policing, and hot spot policing models was also identified, meaning that usually two or more of these approaches were used in conjunction. The analysis of the keywords showed that three main policing models exist today: community policing, predictive policing and evidence-based policing.